Comparative Nutritional Profiling of Leucaena leucocephala (Wondergraze and Taramba varieties) for Enhanced Animal Feed Applications - Firstca Aulia Rachma; Nurain Aziman; Norizan Ahmat; Neni Kartini; Agustono Wibowo (International Journal of Science and Environment (IJSE), 2026)
Leucaena leucocephala belongs to the family Leguminosae and is one of the fastest-growing leguminous trees. L. leucocephala leaves have a great potential as an alternative protein source for animal feed. However, the presence of anti-nutritional compounds, such as mimosine and tannins, limits their direct utilisation by animals, as these compounds can reduce nutrient digestibility and impair animal performance. Ensiling has been widely recognised as an effective processing method to reduce these compounds. This study evaluated the proximate composition, fibre fractions, mineral composition, and anti-nutritional compounds of unensiled (fresh) and ensiled L. leucocephala leaves from Wondergraze and Taramba varieties to assess their potential as animal feed resources. Overall, the ensiling process significantly influenced the nutritional profiles of L. leucocephala leaves in both Wondergraze and Tarramba varieties. Ensiling enhanced crude protein content while reducing crude fibre, NDF and moisture levels, indicating improved digestibility and feed intake potential. Although slight reductions in ash content, gross energy and certain minerals were observed, most nutrients were largely retained, suggesting that fermentation did not compromise the overall nutritional value of the forage. Varietal differences were evident, with Wondergraze demonstrating better fibre preservation and smaller energy losses compared to Tarramba, highlighting its potentially superior fermentation efficiency. Importantly, ensiling markedly reduced anti-nutritional compounds, particularly mimosine and tannins, thereby improving feed safety and suitability. These findings demonstrate that ensiling is an effective processing method to enhance the nutritional quality and practical utilisation of L. leucocephala leaves as animal feeds, while also revealing cultivar-specific responses that are valuable for targeted feed formulation and forage management strategies.